Nominacja biskupia księdza Karola Radońskiego i jej kontekst prasowy - Szczepaniak, Maciej (Ecclesia. Studia z Dziejów Wielkopolski, 2010)
In April 1927 the Holy Father Pious XI appointed Rev. Karol Radoński, pastor of the church of the Most Holy Heart of Jesus and St. Florian in Poznań, coadjutor bishop of August Hlond, the archbishop of Gniezno and Poznań. In the literature of the subject it is assumed that the Episcopal nomination took place on 8 April, 1927, even though from an analysis of press accounts of the period it follows that the news was made public only on 22 April. The article, based on source documents, describes the circumstances of the nomination of Rev. K. Radoński as coadjutor bishop and the press context of the event. The nomination was preceded by a press leak about Rev. Józef Kłos, editor-in-chief of , Przewodnik Katolicki" as supposedly suggested for the post by Primate Hlond.